The Analysis of Grief in Chukwu’s Till and Braff’s A Good Person: A Comparative Analysis - Dewi, Nadia Septian Kumala; Andayani, Ambar (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study aims to compare grief in Chinonye Chukwu’s Till and Zach Braff’s A Good Person. This study applies a comparative literary approach supported by psychological theory, specifically William Worden’s Four Tasks of Mourning, to examine how grief is experienced, expressed, and resolved by the main characters. This study also uses a descriptive qualitative method. The analysis focuses on the similarities and differences in the cause of grief, tasks of grief, and the impact of grief. Mamie grieves the brutal murder of her son and transforms her sorrow into activism and justice, while Allison struggles with guilt after causing a tragic accident and begins a journey toward personal healing. The findings reveal that both characters experience the tasks of grief: accepting the reality of the loss, processing the pain, adjusting to a new reality, and finding an enduring connection, though in different ways. Although both characters experience similar grief processes, the expression and impact of grief differ significantly. Physically, emotionally, socially, and spiritually, each character is affected in distinct ways depending on their background and the nature of their loss. Keywords: Comparative Literature, Grief, Task of grief, Impact of grief, Till